Megaesophagus Secondary to Anastomoses Stenosis in a Patient Previously Gastrectomized (Billroth II) - Rompani, Omar C; Rompani, Omar C; Delbene, Roberto; Bogliaccini, Gustavo (Cirugía del Uruguay, 1981)
A patient who had undergone gastrectomy and re• gastrectomy ( Billroth II) presented a late benign stenosis of anastomoses with megaesophagus secondary to it. A gastrectomy was again performed with excellent evolution. Histological tests indicated fibrous stricture of anastomoses. The megaesophagus disappeared